Los documentos de la conciliación extrajudicial en sede judicial - Arenas Correa, José David (Revista CES Derecho, 2018)
El presente artículo explorará la solución de vacíos a ciertas situacionesdonde pretende darse algún valor procesal a las actas o constancias deaudiencias de conciliación extrajudicial en derecho celebradas al amparode la ley 640 de 2001 en asuntos de Derecho Privado.Se recurrirá al método integrativo del derecho, con la idea de que, de lasmismas fuentes del derecho directas o fuertes, auxiliares o suaves, surgensoluciones sobre casos concretos que pueden acaecer cuando las actasvan a acabar instrumentalizadas en procesos judiciales.El presente documento constituye una línea de pensamiento integrada aotro artículo ya publicado en la Revista CES Derecho1 sobre casos de asistenciaa audiencias de conciliación extrajudicial en Derecho, preocupándoseya en esta sede sobre el valor probatorio y la utilidad de los documentosque acaban sirviendo de actas o constancias de las referidas audiencias.Todas las respuestas otorgadas a la temática en el presente texto correspondenal sentido integrativo interpretativo del autor. The documents of the extrajudicial settlement in judicial headquarters This paper will explore the solution to legal-empties for the resolution ofcertain situations that occur where some evidential value is intended to begiven to the conciliatory records or absence records of out-court legal conciliationhearings under the act 640 of 2001 in relation of matter of Private Law.For the solution of concrete cases shall be referred to the Law´s integrativemethod, under the idea that the same sources of direct, hard, auxiliary orsoft-law solutions on disparate circumstances arise that may happen whenthe minutes will end up instrumentalized in judicial processes. This document constitutes a line of thought integrated another article alreadypublished in CES Law Review on cases of assistance to hearings ofout-of-court conciliation in law, worrying already in this venue about theprobative value and the utility of the documents that end up serving asminutes or records in the hearings. All answers given to the subject in this text, obey the integrative interpretative senseof the author. Keywords: Extra court conciliation hearing, Proofs – evidential material, ColombianAct 640 of 2001, Conciliation Center, Alternative Dispute Resolution Mechanisms(ADRM). DOI: http://dx.doi.org/10.21615/cesder.9.1.6